Decline of cognitive and behavioral functions in amyotrophic lateral sclerosis: a longitudinal study. Issue 5 (2nd July 2020) - Bersano, Enrica; Sarnelli, Maria Francesca; Solara, Valentina; Iazzolino, Barbara; Peotta, Laura; De Marchi, Fabiola; Facchin, Alessio; Moglia, Cristina; Canosa, Antonio; Calvo, Andrea; Chiò, Adriano; Mazzini, Letizia
Abstract: Background : A cognitive impairment, ranging from frontotemporal dementia (FTD) to milder forms of dysexecutive or behavioral dysfunction, is detected in 30–50% of patients affected by amyotrophic lateral sclerosis (ALS) at diagnosis. Such condition considerably influences the prognosis, and possibly impacts on the decision-making process with regards to end-of-life choices. The aim of our study is to examine the changes of cognitive and behavioral impairment in a large population of ALS from the time of diagnosis to a 6-month follow-up (IQR 5.5–9.0 months), and to examine to what extent the progression of cognitive impairment affects survival time and rate of disease progression. Methods : We recruited 146 ALS patients classified according to revised criteria of ALS and FTD spectrum disorder. In a multidisciplinary setting, during two subsequent visits we examined clinical features with ALSFRS-r score, FVC% and BMI, and cognitive status with an extensive neuropsychological evaluation. Results : At second examination, one-third of patients showed a worsening of cognitive impairment, namely 88% of ALSbi, 27% of ALSci, 40% of ALScbi, and, interestingly, also 24% of cognitive normal ALS developed a significant cognitive dysfunction. We find that those who changed their cognitive status presented a lower ALSFRS-r score at t1 and a shorter survival time compared to those who did not change, regardless of the type of cognitive impairment. Conclusion : We show how cognitive disorders in ALS patients can not only be present at diagnosis, but also manifest during disease and influence the progression of motor deficit and the prognosis.